PENGARUH GAYA KEPEMIMPINAN DAN DUKUNGAN ORGANISASI SERTA KEPUASAN KERJA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN BANKALTIMTARA CABANG TENGGARONG - WENTY ANGGRAINI; Prof. Dr. Sukisno S. Riadi; Dr. Irwan Gani, M.Si (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACT EFFECT OF LEADERSHIP AND ORGANIZATION SUPPORTWORK SATISFACTION WITH EMPLOYEE MOTIVATION AND EMPLOYEE PERFORMANCE BANKALTIMTARA BRANCH TENGGARONG Wenty Anggraini1501026156 Bankaltimtara Tenggarong Branch has an employee of 128 people with a declining discipline level, and employee turnover rates tend to increase. This condition is feared will make employee performance will decrease, so that in turn will disrupt the performance of Bankaltimtara Tenggarong Branch.This phenomenon is the focus of research, so the purpose of research is to know and analyze the influence of leadership style and organizational support, and job satisfaction on work motivation and employee performance Bankaltimtara Tenggarong Branch. Data obtained from all employees Bankaltimtara Tenggarong Branch, through the instrument questionnaire. Data, then processed by using partial least square research model (PLS), through the help of statistical applications SmartPLS.The results of research indicate that leadership style and job satisfaction have positive and significant impact on work motivation and employee performance of Bankaltimtara Tenggarong Branch. Another result is, organizational support also positively affects the performance of Bankaltimtara Tenggarong Branch. Nevertheless, the dunkungan of the organization turned out to have a positive but not significant effect on work motivation, although positively, but not significantly to the employee performance of Bankaltimtara Tenggarong Branch.Referring to the results of research, it is advisable to Bankaltimtara Branch Tenggarong some things, namely; the need for socialization of the values and codes of ethics and corporate governance, in addition to modeling in its application to employees. In addition, to better motivate employees to perform high, neither ignore the intrinsic types of motivation such as rewarding, fun co-workers, or participating in decision-making